IDENTIFIKASI PENYAKIT TIDAK MENULAR (PTM) MELALUI KADAR GULA DARAH, ASAM URAT, KOLESTEROL PADA MASYARAKAT DI KELURAHAN SUKAJAYA - Mayumi Gultom, Venny; Kurniawan, C. Evi (Jurnal Kesehatan dan Pembangunan, 2025)
Indonesia is facing an increase in the burden of non-communicable diseases. The increase in the prevalence of non-communicable diseases (NCDs) is closely related to lifestyle patterns, such as smoking habits, lack of physical activity, and low consumption of fruits and vegetables. The non-communicable diseases that need to be prevented are diabetes mellitus, gout, and cholesterol. Routine health check-ups following the CERDIK behavior are very important for early detection of disease symptoms and simultaneously reducing treatment costs. The purpose of this research is to identify NCDs through the blood sugar levels, uric acid, and cholesterol of the community. This research is a quantitative study with a cross-sectional design. The population is all residents in the Research area. The sample used in this study was taken using a predetermined purposive sampling technique, amounting to 83 people with specified inclusion criteria. The research results found that the blood sugar level 2 hours after eating was in the normal category for 75 people (90.4%), prediabetes for 6 people (7.2%), and diabetes for 2 people (2.4%). The normal range of uric acid levels for men is mostly 29 people (34.9%), with the abnormal category being ? 7mg/dL for 15 people (18.1%). For women, the normal range is 30 people (36.1%), with the abnormal category being (? 6 mg/dL) for 10.8%. Cholesterol in the blood is mostly within the normal range of ? 200 mg/dL, with 57 people (68.7%) in the normal category and 26 people (31.3%) in the moderate category. It is recommended for the public to regularly undergo independent laboratory tests or visit the nearest healthcare facility, pay attention to a healthy lifestyle, such as consuming nutritious food and exercising regularly.